2015
DOI: 10.1155/2015/714149
|View full text |Cite
|
Sign up to set email alerts
|

Development of Urban Road Network Traffic State Dynamic Estimation Method

Abstract: Traffic state estimation is a key problem with considerable implications in modern traffic management. A simple, general, and complete approach to the design of urban network traffic state and phase estimator has been developed in this paper. A uniform traffic state dynamic estimation method structure is designed which consists of three steps. (1) Floating-car data and radio frequency identification data preprocessing method is proposed to remove the abnormal data and finish the map matching process. (2) Secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, Many traffic flow models [ 18 29 ] have been proposed to study complex traffic conditions. The present study employs the velocity of the traffic flow on a road segment, as in some previous studies [ 1 , 13 , 14 , 30 , 31 ]. The floating cars are part of the traffic flow; hence, it is reasonable to consider their speed as the speed of the traffic flow.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Furthermore, Many traffic flow models [ 18 29 ] have been proposed to study complex traffic conditions. The present study employs the velocity of the traffic flow on a road segment, as in some previous studies [ 1 , 13 , 14 , 30 , 31 ]. The floating cars are part of the traffic flow; hence, it is reasonable to consider their speed as the speed of the traffic flow.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…In order to improve the quality of the raw data to achieve more accurate prediction results, according to the missing characteristics, the original data are divided into accidental missing and multiple missing. Referring to related literature, it is found that the naive Bayesian method and dynamic time warping method can be used to repair these two types of missing data, respectively, with good performance [36][37][38]. Consequently, we choose the naive Bayesian method and dynamic time warping method to estimate the two types of missing data separately, obtaining a complete dataset without abnormal points, which lays a solid foundation for the subsequent prediction of short-term traffic speed.…”
Section: Data Quality Improvementmentioning
confidence: 99%
“…In real-world conditions, traffic demand significantly fluctuates over time. Traffic flow may vary greatly even at the same time of the day or the same day of the week [5,6]. If only a fixed flow is used as the timing basis, the timing scheme will be susceptible to flow fluctuation, resulting in poor control reliability [7].…”
Section: Introductionmentioning
confidence: 99%